2014
DOI: 10.1021/cb500316h
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of 2-Amino-4-phenylthiazole Inhibitors of the HIV-1 Nucleocapsid Protein with Antiviral Activity

Abstract: The nucleocapsid protein (NC) is a highly conserved protein in diverse HIV-1 subtypes that plays a central role in virus replication, mainly by interacting with conserved nucleic acid sequences. NC is considered a highly profitable drug target to inhibit multiple steps in the HIV-1 life cycle with just one compound, a unique property not shown by any of the other antiretroviral classes. However, most of NC inhibitors developed so far act through an unspecific and potentially toxic mechanism (zinc ejection) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
5
29
0
Order By: Relevance
“…This initial group of putative ligands was docked by following the same criteria to the receptor structures described above. The process yielded a series of nineteen analogues of compound 5 (named 5-01 to 5-19, Figure 2), which included both benzoxazolinone and benzimidazolinone structures that were able to fit the NC hydrophobic pocket and establish H-bonds with key NC residues [3,12,14,15]. These compounds were further evaluated for their NC inhibition activity.…”
Section: Optimization Of Benzoxazolinone Derivatives Improved Their Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial group of putative ligands was docked by following the same criteria to the receptor structures described above. The process yielded a series of nineteen analogues of compound 5 (named 5-01 to 5-19, Figure 2), which included both benzoxazolinone and benzimidazolinone structures that were able to fit the NC hydrophobic pocket and establish H-bonds with key NC residues [3,12,14,15]. These compounds were further evaluated for their NC inhibition activity.…”
Section: Optimization Of Benzoxazolinone Derivatives Improved Their Nmentioning
confidence: 99%
“…A more promising alternative consists of possible competitive inhibitors that may be capable of interfering with the binding of NC to typical nucleic acid substrates [3]. Indeed, it has been shown that the hydrophobic pocket, which forms when the ZF domains are brought close together, for example, by interacting with an exposed guanine nucleobase on cognate nucleic acid substrates, can establish stable interactions with small molecule ligands [12][13][14]. Although such compounds have been touted as possible modulators of NC-nucleic acid interactions, no drug candidate has emerged thus far.…”
Section: Introductionmentioning
confidence: 99%
“…1d-h, these residues are among those involved in NA binding. However, only a residual antiretroviral activity was observed in HIV-1 LAI MAGI cells (EC 50 = 95 mM; CC 50 >250 mM) [25]. In 2012, the developed computational methodologies were used to screen the ASINEX database leading to the identification of ten candidates, in turn tested for their ability to inhibit viral replication through the MAGI assay.…”
Section: Hts-derived Small Moleculesmentioning
confidence: 99%
“…The NCI binds in a 2:1 ratio in a hydrophobic pocket, providing π-π stacking interactions with Trp37, thus mimicking the guanosine base of the NC nucleic acid binder. Facilitated by the NMR high-resolution structure, rational optimization in silico resulted in the generation of AN3 (2-amino-4-phenylthiazole NCI), an efficient, non-toxic NCI with antiviral activity in cells [141]. Taken together, these structures provided important insights and supported the drugability of NC towards more improved and efficient drug-like NCIs.…”
Section: Small Molecules As Non-zinc Ejectorsmentioning
confidence: 90%